Inattention, emotion dysregulation and impairment among urban, diverse adults seeking psychological treatment. (December 2019) - O'Neill, Sarah; Rudenstine, Sasha
Highlights: Participants were clients attending a low-fee outpatient mental health clinic. Participants self-reported inattention, emotion regulation skills and impairment. Inattention affected distress and relationships through emotion dysregulation. Most important were identifying one's feelings; strategies to modulate emotions. Only inattention was related to impairment at school and work. Abstract: Emotion dysregulation is commonly reported among adults with Attention-Deficit/Hyperactivity Disorder. This study examined whether inattention and/or hyperactivity/impulsivity directly affect functional impairment, or whether they do so indirectly by decreasing emotion regulation capabilities. An ethnically, racially and socioeconomically diverse sample of clients seeking treatment at a low-fee outpatient mental health clinic were recruited [ N = 177, male n = 59, 33.3%, mean (SD) age = 28.54 (8.41) years]. Participants completed measures of inattention, hyperactivity/impulsivity, emotion regulation and impairment at intake. Inattention was more strongly related to emotion regulation and impairment than hyperactivity/impulsivity. Hayes' PROCESS was used to test for significant indirect effects. More severe inattention was associated with less emotional clarity, which in turn was associated with worse Interpersonal Relationship difficulties; more severe inattention was associated with less access to emotion regulation strategies and poorer emotional clarity, which in turn were associated with greater Symptom Distress; and inattention was directly associated with impairment at school and work. In addition to treating inattention, clinicians should focus on emotion regulation deficits. Specifically, working with individuals to improve identification and labeling of emotions, develop strategies to reduce the intensity of their negative emotions, and feel more confident that they have these tools at their disposable may help to reduce impairment.